Treatments for Biomedical Abnormalities Associated with Autism Spectrum Disorder - Frye, Richard Eugene; Rossignol, Daniel A. (Frontiers in Pediatrics, 2014)
Recent studies point to the effectiveness of novel treatments that address physiological abnormalities associated with autism spectrum disorder (ASD). This is significant because safe and effective treatments for ASD remain limited. These physiological abnormalities as well as studies addressing treatments of these abnormalities are reviewed in this article. Treatments commonly used to treat mitochondrial disease have been found to improve both core and associated ASD symptoms. Double-blind, placebo-controlled studies have investigated L-carnitine and a multivitamin containing B vitamins, antioxidants, vitamin E, and coenzyme Q10 while non-blinded studies have investigated ubiquinol. Controlled and uncontrolled studies using folinic acid, a reduced form of folate, have reported marked improvements in core and associated ASD symptoms in some children with ASD and folate related pathways abnormities. Treatments that could address redox metabolism abnormalities include methylcobalamin with and without folinic acid in open-label studies and vitamin C and N-acetyl-L-cysteine in double-blind, placebo-controlled studies. These studies have reported improved core and associated symptoms with these treatments. Lastly, both open-label and double-blind, placebo-controlled studies have reported improvement in core and associated ASD symptoms with tetrahydrobiopterin. Overall, these treatments were generally well tolerated without significant adverse effects for most children, although we review the reported adverse effects in detail. This review provides evidence for potential safe and effective treatments for core and associated symptoms of ASD that target underlying known physiological abnormalities associated with ASD. Further research is needed to define subgroups of children with ASD in which these treatments may be most effective as well as confirm their efficacy in double-blind, placebo-controlled, large-scale multicenter studies.